TRBC1 in flow cytometry: Assay development, validation, and reporting considerations - Katherine Devitt; Wolfgang Kern; Weijie Li; Xuehai Wang; Allyson J. Wong; Felipe Magalhães Furtado; Jean Oak; Andrea Illingworth (2024)
Abstract The assessment of T‐cell clonality by flow cytometry has long been suboptimal, relying on aberrant marker expression and/or intensity. The introduction of TRBC1 shows much promise for improving the diagnosis of T‐cell neoplasms in the clinical flow laboratory. Most laboratories considering this marker already have existing panels designed for T‐cell workups and will be determining how best to incorporate TRBC1. We present this comprehensive summary of TRBC1 and supplemental case examples to familiarize the flow cytometry community with its potential for routine application, provide examples of how to incorporate it into T‐cell panels, and signal caution in interpreting the results in certain diagnostic scenarios where appropriate.